Exploratory study to assess and evaluate requirement specification techniques using analysis determination requirements framework - Besrour, S. (Maxwell Science Publications, 2015)
Various requirements engineering techniques have been proposed to enhance the quality of requirement as well as the implemented software and to growth customer satisfaction with the product. However the large number of requirement techniques makes the choosing between them complicated and confusing. Consequently, this study purposes to present an exploratory study to evaluate requirement techniques and illuminate their key features, limitations and strength. Â© Maxwell Scientific Organization, 2015.